Peasant struggle and violence in the contested region between Espírito Santo and Minas Gerais (Revista de História Regional, 2020)
AbstractTensions by territorial boundary in the contested region between Espírito Santo and Minas Gerais and conflicts over land and power in the period from 1940 to 1962 led to a violence that went beyond the limits of the human condition itself and of life in society. Landowners and squatters sought to usurp the rights of settlers. In the municipality of Ecoporanga, ES, the situation was more brutal with the Military Police carrying out diligence and supporting large landowners.Keywords: contested Region. Violence. Earth. Espírito Santo. Minas Gerais.